A multi‐centre cohort study investigating the outcome of synovial contamination or sepsis of the calcaneal bursae in horses treated by endoscopic lavage and debridement. (16th October 2019) - Isgren, C. M.; Salem, S. E.; Singer, E. R.; Wylie, C. E.; Lipreri, G.; Graham, R. J. T. Y.; Bladon, B.; Boswell, J. C.; Fiske‐Jackson, A. R.; Mair, T. S.; Rubio‐Martínez, L. M.
Summary: Background: Previous studies investigating factors associated with survival following endoscopic treatment of contamination/sepsis of the calcaneal bursa are limited. Objectives: To investigate the factors associated with survival in horses with contamination/sepsis of the calcaneal bursae treated endoscopically and to describe the bacterial isolates involved in the synovial infections. Study design: Retrospective analysis of clinical records. Methods: Medical records from 128 horses with contamination/sepsis of the calcaneal bursae treated by endoscopic lavage at seven equine hospitals were reviewed. A follow‐up questionnaire was used to determine survival and return to athletic performance. Descriptive statistics and Cox proportional hazards survival models were used to determine factors associated with survival. Results: Horses underwent one (n = 107), two (n = 19), or three (n = 2) surgeries. Survival to hospital discharge was 84.4%. Univariable survival analysis revealed that administration of systemic antimicrobials prior to referral was associated with reduced mortality (hazard ratio, [HR] 0.41, 95% CI 0.18–0.91, P = 0.03). Increased mortality was associated with bone fracture/osteomyelitis (HR 2.43, 95% CI 1.12–5.26, P = 0.03), tendon involvement (≥30% cross sectional area) (HR 3.78 95% CI 1.78–8.04, P = 0.001), duration of general anaesthesia (HR 1.01, 95% CI 1.00–1.02, P = 0.04), post‐operative synoviocentesis (HR 3.18, 95% CI 1.36–7.43, P = 0.006) and post‐operative wound dehiscence (HR 2.5, 95% CI 1.08–5.65, P = 0.04). Multivariable Cox proportional hazards model revealed reduced mortality after systemic antimicrobial administration prior to referral (HR 0.25, 95% CI 0.11–0.60, P = 0.002) and increased mortality with tendinous involvement (≥30% cross‐sectional area) (HR 7.92, 95% CI 3.31–19.92, P<0.001). At follow‐up (median 30 months, range 0.25–13 years, n = 70) 87.1% horses were alive, 7.1% had been euthanised due to the calcaneal injury and 5.7% had been euthanised for unrelated reasons. From 57 horses with athletic performance follow‐up, 91.2% returned to the same/higher level of exercise, 5.3% to a lower level and 3.5% were retired due to persistent lameness of the affected limb. Main limitations: Retrospective study and incomplete follow‐up. Conclusion: Endoscopic treatment of contamination/sepsis of the calcaneal bursae has an 84% survival rate to hospital discharge. Tendinous involvement reduced survival whilst systemic antimicrobials administration prior to referral improved survival.